Isotope discrimination and photosynthesis of vegetation growing in the Bossoleto CO 2 spring (Chemosphere, 1998)
The Bossoleto CO2 spring emits CO2 which has a stable carbon isotopic ratio (~5~3C = - 8%o). We determined ~3C on leaves of several individual species growing in Bossoleto and in a nearby control site at ambient CO,.. ~5t3C was 6% more negative in leaves of species collected from the grassland community of Bossoleto, indicating increased discrimination (A) against the heavy carbon isotope. No such changes were found in ruderal species growing in the same spring, suggesting that photosynthetic capacity was much less affected. A was substantially increased under elevated CO2 in leaves of Quercus pubescens but not in Quercus ilex, which also did not show any increase in non-structural carbohydrates. Gas-exchange measurements made on Plantago lanceolata, supported the view that photosynthetic capacity is decreased in plants grown under elevated CO: and on poor soils

Morphological adjustments of mature Quercus ilex trees to elevated CO 2 (Acta Oecologica, 1997)
It is still not known whether mature forest trees respond to increasing atmospheric CO 2 concen- trations in similar ways as seedlings do. Mature Mediterranean oaks (Qaercus ilex) growing in a CO 2 enriched atmosphere around natural CO 2 vents since the seedling stage showed a moderate, age- dependent increase in stem biomass production, but had significantly lower biomass of 6-year-old branches, decreased branching, and lower leaf area per unit branch biomass, compared to control trees at a nearby unenriched site. Our data indicate that trees in natural forest stands morphologically adjust to increasing CO 2 and reduce COz-induced initial growth stimulations. Allometric adjustments such as reduction in leaf area may be regarded as a "down-regulation" of canopy photosynthesis and may be an effective mechanism for saving water.

Thirty years of in situ tree growth under elevated CO2: a model for future forest responses? (GLOBAL CHANGE BIOLOGY, 1997)
Rising concentrations of atmospheric carbon dioxide have been predicted to stimulate the growth of forest trees. However, long-term effects on trees growing to maturity and to canopy closure while exposed to elevated CO2 have never been examined. We compared tree ring chronologies of Mediterranean Quercus ilex which have been continuously exposed to elevated CO2 (around 650 mu mol mol(-1)) since they were seedlings, near two separate natural CO2 springs with those from trees at nearby ambient-CO2 `control' sites. Trees grown under high CO2 for 30 years (1964-93) showed a 12% greater final radial stem width than those growing at the ambient-CO2 control sites. However, this stimulation was largely due to responses when trees were young. By the time trees were 25-30 y old the annual difference in tree ring width between low and high CO2 grown trees had disappeared. At any given tree age, elevated CO2 had a relatively greater positive effect on tree ring width in years with a dry spring compared to years with more rainfall between April and May. This indicates a beneficial effect of elevated CO2 on tree water relations under drought stress. Our data suggest that the early regeneration phase of forest stands can be accelerated in CO2-enriched atmospheres and that maximum biomass per land area may be reached sooner than under lower CO2 concentrations. In our study, high CO2 grown Q. ilex trees reached the same stem basal area at the age of 26 y as control trees at 29 y,i.e. three years earlier (faster turnover of carbon?). Reliable predictions of the future development of forests need to account for the variable responses of trees over their entire lifetime. Such responses to elevated CO2 can presently only be assessed at such unique field sites.

Long term effects of naturally elevated CO 2 on mediterranean grassland and forest trees (Oecologia, 1994)
We investigated the carbon supply status in species-rich mediterranean plant communities growing in a bowl-shaped 1-ha "CO2 spring" area near Sienna, Italy. A geothermic "lime-kiln" has provided these communities, for as long as historical records are avail- able, with pure CO2 that mixes with ambient air at canopy level to daytime means of 500-1000 ppm CO2. Immediately outside the spring area similar plant com- munities are growing on similar substrate, and in the same climate, but under ca. 355 ppm CO2. We found no evidence that plants in the CO2 spring area grow faster, flower earlier or become larger. However, we found very large differences in tissue quality among the 40 species studied inside and outside the spring area. Depending on weather conditions, the mean concentra- tion of total non-structural carbohydrates (TNC, sugars and starch) in leaves of herbaceous plants was 38-47% higher in the spring area. Fast growing ruderals growing on garden soil inside and outside the spring area show the same response. Among trees, leaves of the deciduous Quercus pubscens contain twice as much TNC inside as outside the vent area, whereas evergreen Q. ilex leaves show no significant difference. TNC levels in branch wood paralleled leaf values. TNC in shade leaves was also higher. Elevated CO2 had no effect on the sugar fraction, therefore differences in TNC are due to starch accumulation. Leaf nitrogen concentration decreases under elevated CO2. These observations suggest that the commonly reported TNC accumulation and N depletion in leaves growing under elevated CO2 are not restricted to the artificial condi- tions of short-term COz enrichment experiments but persist over very long periods. Such an alteration of tissue composition can be expected to occur in other plant communities also if atmospheric COz levels con- tinue to rise. Effects on food webs and nutrient cycling are likely